Nodulation and symbiotic nitrogen fixation in bean with rhizobium native strains, in soil amended with sewage sludge - Vieira, Rosana Faria; Tsai, Siu Mui; Teixeira, Manoel Araújo (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0; @font-face font-family:"\@Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; color:windowtext; mso-ansi-language:PT-BR; p margin-right:0cm; mso-margin-top-alt:auto; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Arial Unicode MS"; color:black; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –>The objective of this work was to evaluate the effect of sewage sludge soil amendment, on nodulation and N2 fixation on bean nodulated with native rhizobia in greenhouse. Treatments were: no fertilization and no sludge; complete fertilization; 14.8 t ha-1, 29.6 t ha-1 and 59.2 t ha-1 of sewage sludge; and bean inoculated with selected rhizobia strains+N at planting. The doses of sewage sludge were calculated based on N crop requirement. The highest values obtained with the acetylene reduction activity, nodule number and mass by doses 14.8 t ha-1 and 29.6 t ha-1 of sludge demonstrated that soil amendment with sludge may increase bean native rhizobia efficiency. <!–[if !supportEmptyParas]–> <!–[endif]–>